UPAYA REHABILITASI EKS PEKERJA SEKS KOMERSIAL (PSK) DI PANTI SOSIAL KARYA WANITA (PSKW) ANDAM DEWI SOLOK - Ahmad Saefulloh; Nofriza Nofriza (Institut Agama Islam Negeri Palopo, 2018)
This study aims to see the rehabilitation efforts of former Sex Workers Commercial (PSK) in Panti Sosial Karya Wanita (PSKW) Andam Dewi Solok. The large number of sex workers becomes a serious problem that must be followed up immediately. The Crowd raids prostitution reported in the media into the spotlight of the world of education in instilling moral education to learners. This is the importance of recognizing the negative impacts. To avoid the proliferation of the practice of prostitution is necessary to preventive and rehabilitative efforts against the perpetrators of prostitution practices that netted raids. This study aims to provide a form of preventive and rehabilitative efforts for the